2021
DOI: 10.2147/jir.s343956
|View full text |Cite
|
Sign up to set email alerts
|

A Next-Generation Sequencing of Plasma Exosome-Derived microRNAs and Target Gene Analysis with a Microarray Database of Thermally Injured Skins: Identification of Blood-to-Tissue Interactions at Early Burn Stage

Abstract: Background Plasma exosome-derived microRNA (miRNA) profiles following thermal injury and their relationship with gene expression derangements in burned skin remain unexplored. This study focused on the identification of key miRNA-mRNA axes in potential blood-to-tissue interactions at early burn stage. Methods Plasma exosomes were obtained from 6 severe burn patients 4–7 days post injury and 6 healthy volunteers. Next-generation sequencing (NGS) of exosomal small RNAs pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Together with the in vivo result, these observations indicated an intercellular communication between microglia and neurons. In the past few years, exosomes carrying proteins, miRNAs and other bioactive substances have been widely regarded as a transporter for intercellular signal transduction (Li et al., 2021; Zhou et al., 2020). miRNAs can be encapsulated by exosomes and freely cross the blood–brain barrier, and therefore this is a potential strategy to target the RVLM region through this pathway without brainstem injections, which would increase translatability into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the in vivo result, these observations indicated an intercellular communication between microglia and neurons. In the past few years, exosomes carrying proteins, miRNAs and other bioactive substances have been widely regarded as a transporter for intercellular signal transduction (Li et al., 2021; Zhou et al., 2020). miRNAs can be encapsulated by exosomes and freely cross the blood–brain barrier, and therefore this is a potential strategy to target the RVLM region through this pathway without brainstem injections, which would increase translatability into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared to local damage caused by mechanical injury, the permeability of burns has a systemic effect on the body. RNA-sequencing-based studies have found that plasma exosome-derived microRNA profiles are altered after thermal injury, which may be an important cause of disordered skin gene expression in the early burn stage 168 , 169 . Protein profiling-based studies have found that burns induce significant changes in serum exosomal protein function, altering enzyme inhibitor activity, heparin-binding, coagulation, and lipid transport 170 .…”
Section: Introductionmentioning
confidence: 99%